2015
DOI: 10.5830/cvja-2015-047
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ginseng extracts and common anti-aggregant drugs on ischaemia-reperfusion injury : cardiovascular topics

Abstract: SummaryObjectiveGinseng is a traditional herbal medicinal product widely used for various types of diseases because of its cellular protective effects. Possible protective effects of ginseng were investigated in blood, cardiac and renal tissue samples and compared with common anti-aggregant agents in an animal ischaemia–reperfusion (I/R) model.MethodsTwenty rats were equally divided into four different groups as follows: control group (I/R-induced group without drug use), group I (acetylsalicylic acid-administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In rats with myocardial ischemia, treatment with flaxseed in combination with exercise recovered the decreased PON1 and HDL levels, whereas administration of flaxseed alone had no effect [ 31 ]. In a rat ischemia–reperfusion model, significant decreases were observed in the serum PON1 levels of animals given ginsenoside despite the decrease in malonyldialdehyde [ 32 ]. In contrast, the decrease of PON1 and arylesterase activities in arthritis-induced rats was restored after treatment with soy protein and isoflavone (genistein and daidzein) for 50 days [ 33 ].…”
Section: Plant Preparationsmentioning
confidence: 99%
“…In rats with myocardial ischemia, treatment with flaxseed in combination with exercise recovered the decreased PON1 and HDL levels, whereas administration of flaxseed alone had no effect [ 31 ]. In a rat ischemia–reperfusion model, significant decreases were observed in the serum PON1 levels of animals given ginsenoside despite the decrease in malonyldialdehyde [ 32 ]. In contrast, the decrease of PON1 and arylesterase activities in arthritis-induced rats was restored after treatment with soy protein and isoflavone (genistein and daidzein) for 50 days [ 33 ].…”
Section: Plant Preparationsmentioning
confidence: 99%
“…Between‐group analyses indicated that GLP supplementation was associated with the increased levels of SOD, GSH‐PX, TAC and PON1, of which significant associations was found between PM 2.5 exposure and elevated levels of serum SOD and PON1. Numbers of studies have shown that ginseng, Lilii Bulbs or Poria have beneficial effects against oxidative stress (Caliskan et al, 2015; Hussein et al, 2016; Ramesh et al, 2012; Wang et al, 2012; Xu et al, 2016; Yousef & Hussien, 2015). Rats treated with ginseng prior to cisplatin [received ginseng (100 mg/kg BW/day) orally for 15 consecutive days in addition to cisplatin (7.5 mg/kg BW) as a single intraperitoneal dose on the 10th day of the experiments 1 hr prior to ginseng dose] exhibited a significant ( p < .05) increase in the activities of antioxidant enzymes (SOD, GSH‐PX) compared to rats receiving cisplatin alone (received a single intraperitoneal dose of cisplatin 7.5 mg/kg BW on the 10th day of the experiment), which can be concluded that the protective effects of ginseng against cisplatin induced‐renal damage was associated with the attenuation of oxidative stress and the preservation of antioxidant enzymes (Yousef & Hussien, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages, insulin resistance is countered by high insulin secretion. However, advanced damage of β-cell mass and function restricts the ability of the pancreas to control the presence of glucose in the blood by rising insulin secretion (7). The first obvious sign of hyperglycemia due to prediabetes is impairment of postprandial glucose control but normal and/ or impaired fasting plasma glucose.…”
Section: Contextmentioning
confidence: 99%